Klasifikasi Indeks Standar Pencemaran Udara Menggunakan Algoritma Catboost Dengan Teknik Balancing Data Random UnderSampling - Aditya, Aldy; Umbara, Fajri Rakhmat; Sabrina, Puspita Nurul (Jurnal Algoritma, 2025)
Air quality is an important factor that affects public health and the environment. The Air Pollution Index is used as an indicator to measure the level of air pollution in a region. The main challenge in the air quality classification process is the imbalance of data that can affect the modeling results. This study aims to analyze the performance of the Categorical Boosting (CatBoost) algorithm in ISPU classification by applying the Random Under sampling technique to overcome class imbalance. The dataset used was obtained from air quality monitoring in DKI Jakarta for the period 2020–2024 with a total of 5,386 records and 12 attributes. The research stages included data collection, data cleaning, data transformation, data balancing, feature selection using Recursive Feature Elimination (RFE), modeling with CatBoost, and model evaluation using a confusion matrix. The feature selection results showed five main features that had the most influence, namely PM10, PM2.5, SO2, NO2, and max. The CatBoost model built with the best parameters produced an accuracy of 98 percent, precision of 100 percent, recall of 98.91 percent, and an F1-score of 99.44 percent. Thus, the application of CatBoost and Random Under sampling techniques proved to be effective in improving ISPU classification performance. The results of this study are expected to be used as a decision support system in efforts to mitigate the impact of air pollution in DKI Jakarta.